Are the Beneish model and restatement relevant in detecting tax evasion? - Challista Christabella; Ayu Fury Puspita (Universitas Muhammadiyah Yogyakarta, Indonesia, 2025)
Research aims: This study aims to analyze the capability of fraud pentagon theory’s factors—including pressure, opportunity, rationalization, competence, and arrogance—in indicating tax evasion.Design/Methodology/Approach: The data were analyzed by logistic regression, and the samples of basic material entities listed on the Indonesia Stock Exchange for 10 years, from 2012 to 2021, were selected through the purposive sampling method. The dependent variable of tax evasion indication was measured by Beneish M-score and restatement methodsResearch findings: The results of this study exhibit that pressure represented by financial stability and financial targets proves to indicate tax evasion, while the opportunity (represented by the nature of the industry and ineffective monitoring), rationalization (represented by audit opinion), competence (represented by change in directors), and arrogance (represented by dualism position) do not prove to indicate tax evasion. Theoretical contribution/Originality: Providing additional empirical evidence on the application of the Fraud Pentagon Theory for detecting tax evasion through the integration of the Beneish model and restatement methods.Practitioner/Policy implication: This research can be used by taxpayers, tax officers, tax examiners, and auditors to detect and reduce tax evasion in Indonesia.Research limitation/Implication: The limitations of this study can be seen in the results of the determination coefficient, which is quite low, so there are still other indicators that cannot be explained through this study.